2022
DOI: 10.1038/s41598-022-24572-0
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial etiology and risk factors among newborns suspected of sepsis at Hawassa, Ethiopia

Abstract: Neonatal sepsis is a systemic infection that occurs at an early age. Its etiology varies from one region to the other. The contribution of sepsis to neonatal mortality and morbidity is significant in resource-limited countries; however, there is limited information about the etiology of sepsis in Sidama Regional State, Ethiopia. The aim of this study was to determine the prevalence of bacterial caused newborn sepsis, associated factors, and the antimicrobial susceptibility profile of bacteria. A hospital-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
(47 reference statements)
2
3
0
Order By: Relevance
“…Female newborns were predominant in this study compared to male newborns (52.7% vs. 47.3%). This result was in line with a study conducted by Worku et al, which showed that female newborns were the dominant population [ 26 ]. But it was contrary to studies conducted by Kurma et al, Agnche et al, and Guo et al (2019), which showed otherwise [ 19 , 24 , 27 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Female newborns were predominant in this study compared to male newborns (52.7% vs. 47.3%). This result was in line with a study conducted by Worku et al, which showed that female newborns were the dominant population [ 26 ]. But it was contrary to studies conducted by Kurma et al, Agnche et al, and Guo et al (2019), which showed otherwise [ 19 , 24 , 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…A retrospective study in South Africa also reported that 63.9% of their newborns were born via caesarean section [30]. In contrast, another study conducted in Ethiopia found that most of their study population was born via spontaneous vaginal delivery [26].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations